PENGEMBANGAN DIVERSIFIKASI PRODUK UNTUK MENINGKATKAN EKONOMI DI DESA SUKARAGAM - Apriliani, Adela Dwi; Hasibuan, Akmal Rizki Gunawan; Marginingsih, Ria (An-Nizam, 2024)
Sukaragam Village has the potential to develop a home snack food industry, but so far the products produced are still very simple with low selling value so they have not been able to increase household income significantly. The implementation method includes community education, training, mentoring, and the introduction of appropriate science and technology to PKK mothers in Sukaragam Village. The expected results are an increase in the knowledge and skills of mothers in diversifying processed white bread products as well as the creation of independent household businesses based on pudding and jelly products that are highly competitive. In conclusion, this diversification of household products is expected to increase the added value and income of the Sukaragam Village community.